Social Media as a Factor in Tourism Attraction: A Case Study - Bonilla-Quijada, María; Ripoll-i-Alcon, Joan; del Olmo, Josep Lluís (Street Art & Urban Creativity, 2025)
The field of tourism is one in which social networks have had a considerable impact, both in terms of enabling users to research potential destinations and document their experiences during their travels. Consequently, various tourist destinations have successfully established their positioning and attractiveness within the digital space. A key concept in this field is that of user engagement. This article analyses the official tourism account of the city of Valencia on Instagram. The account was examined over the course of the year 2022, and 362 posts were analysed based on twenty parameters. The study then proceeded to evaluate the account’s ability to generate user reactions in terms of likes, comments and feedback. In the following discussion, the implications for the strategy to promote the tourist attraction of the destination will be considered.